A STUDY TO SEE THE EFFECT OF CHANDRAPRABHA VATI, MADHUHAR YOG AND NIMBADI KASHAY ON BSL IN MADHUMEHA W.S.R NIDDM - Kulkarni Malhar Sharad; Wali Deepak Shivaputra (International Journal of Applied Ayurved Research, 2016)
Diabetes mellitus (DM) is a life style disorder associated with living of the people & burning issue in front of developing India. Although the prevalence of type I & II DM is increasing worldwide, the prevalence of type II DM is expected to rise more rapidly in future because of increase in obesity and reduced physical activity. However, insulin and other oral hypoglycemic drugs have characteristic profile of adverse effects. Ayurveda explained different herbo mineral preparation for successful management. This has initiated this study to see effect of selected combination on BSL in Madhumeha (NIDDM). In the present study, 30 patients of NIDDM are selected and administered selected medicines in order to see the effect on BSL. The results showed highly significant results on BSL and also on the complication like diabetic neuropathy, Nephropathy.